The image of batyr Suranshi in Zh. Zhabaev's poem and historical context (Eurasian Journal of Philology Science and Education, 2023)
A worthy place among the historical figures of Kazakhstan is occupied by batyr and biy Suranshi. As one of the most famous military commanders, patriarchs, diplomats and political actors of his time, i.e. the second-third quarter of the 19th century, Suranshi-batyr attracted natural attention from the point of view of scientific and historical research. However, the artistic image of the batyr, created by akyn Zh. Zhabaev in the poem "Suranshi-batyr", is of no less interest. This article attempts to study the image of Suranshi-batyr in the context of comparison with historical material, as well as to compare the events described in the poem with actual historical phenomena confirmed by scientific sources. The akyn's poem is of interdisciplinary interest from both philological and historical points of view, as a work from the akyn's pre-revolutionary repertoire. Being a long-liver, Zh. Zhabaev in the first decades of his life was a contemporary of the batyr, which necessitates the analysis of the poem as a possible source of information about that period.Given the scientific interest on the part of the academic community, as well as the growing literary, artistic interest and demand for materials on the history of Kazakhstan on the part of artists and civil society, this article seems to be relevant and is an introductory part of subsequent research work on the study of the life and work of famous people of the middle second half of the 19th century.